What primary care health workers know and do about cigarette smoking and cancer risk? - Mevsim, Vildan; Dontlu, Çitim; Yeniçeri, Neşe; Özçakar, Nilgün; Güldal, Dilek (Journal of Dependence, 2005)
Objective: Smoking habit is the most important preventable health problem of the world and Turkey. The objective of this study is to research the knowledge, behavior and attitude of primary care health workers about cigarette smoking and cancer risk. Method: A cross-sectional analytic study is planned. A questionnaire with 82 questions is applied to 142 health workers of 16 primary health care centers in Buca. The questionnaire had three parts including knowledge, behavior and attitude parameters. For each group of parameters a composite index is developed. Data were analyzed on SPSS 11.0 package program by Pearson chi-square, independent t test and Pearson correlation test. Results: In the study, 31% of participants were physicians, 23.2% were nurses, 35.2% were midwives and 10.6% were male-nurses. 36.6% of medical staff were current smokers, 12.0% were ex-smokers. The mean scores of knowledge, behavior and attitude parameters were 20.65 ± 4.81, 6.26 ± 3.51 and 9.73 ± 2.54 in order. There was a statistically significant relation between the attitude and behavior scores (r=0.334 p=0.015). There was no statistically significant relation between knowledge and attitude, behavior scores of participants. Conclusion: Although the health workers have better knowledge and attitude for preventing and decreasing the effects of smoking, they still go on smoking. The health workers must be a good model for the community as non-smokers. Some other ways must be considered to increase awareness and sensitivity of health workers about smoking and cancer.